Laryngeal tuberculosis: report of six cases - Sinan Başoğlu, Mehmet; Aslan, Hale; Eren, Erdem; Songu, Murat; Gürcan Bingölballı, Aslıhan; Kulduk, Erkan; Öztürkcan, Sedat; Katılmış, Hüseyin (ENT Updates, 2012)
The larynx as a site of tuberculosis represents less than 1% of the total of this disease. The incidence of laryngeal tuberculosis is increasing worldwide. Recent studies have described a change in the clinical features of laryngeal tuberculosis. Laryngeal tuberculosis is often misdiagnosed, as it is uncommon. Upper aerodigestive tract tuberculosis is difficult to differentiate from carcinoma; thus, tissue biopsy is necessary for a definite diagnosis. We present six recent cases of laryngeal tuberculosis which its diagnosis was made in all cases through laryngeal biopsy. All were male and their ages ranged from 42-60 years. The prominent presenting symptom was hoarseness. Four patient showed ulcerative lesions, 2 showed pseudo-tumoral images in the larynx. Histopathological results showed granulomatous infectious disease. Chest radiography showed heterogenous density in four of the cases, reticulonoduler density in one, and cavitary, infiltrative lesions in one case. Patients were free of disease after 9 months of tuberculostatic therapy, and laryngeal appearances were almost normal.